2011
DOI: 10.1007/s12041-011-0067-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic admixture studies on four in situ evolved, two migrant and twenty-one ethnic populations of Tamil Nadu, south India

Abstract: We analysed the genetic structure of ≈ 1000 samples representing 27 ethnic groups settled in Tamil Nadu, south India, derived from two linguistic families (Dravidians and Indo-Europeans) representing four religious groups (Hinduism, Islam, Christianity and Jainism) using 11 mtDNA markers. Out of 27 ethnic groups, four are in situ populations (Anglo-Indian, Labbai Muslim, Nadar Christian and south Indian Jain) and two are migrants (Gypsy and north Indian Jain) from north India to Tamil Nadu, and 21 are native e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Moreover, the presence of haplogroup N (which is susceptible to partial AZFc deletions) was traced in the Dravidian population with an estimated frequency range of 5% to 42% (Suhasini et al, 2011). In our study, the frequency of b2/b3 subdeletion was higher compared with the related studies (Repping et al, 2004;Eloualid et al, 2012;Rozen et al, 2012).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Moreover, the presence of haplogroup N (which is susceptible to partial AZFc deletions) was traced in the Dravidian population with an estimated frequency range of 5% to 42% (Suhasini et al, 2011). In our study, the frequency of b2/b3 subdeletion was higher compared with the related studies (Repping et al, 2004;Eloualid et al, 2012;Rozen et al, 2012).…”
Section: Discussionsupporting
confidence: 45%
“…Genetic studies on the present day South Indian population revealed that the population itself is an admixture of various racial groups and shows diverse genetic features (Suhasini et al, 2011). Hence, the information received from the genetic screening studies using well-defined case-control samples will serve as useful reference data in relation to the research, diagnosis, and management of male infertility.…”
Section: Introductionmentioning
confidence: 99%